Hubungan Komunikasi Matematis Dengan Kemampuan Pemecahan Masalah Siswa SMPN 2 Kuripan Tahun Ajaran 2020/2021 - Airma Nurmalasari; Arjudin Arjudin; Nani Kurniati; Sripatmi Sripatmi (Griya Journal of Mathematics Education and Application, 2022)
This study aimed to determine the relationship between mathematical communication and problem solving skills and the level of mathematical communication skills and problem solving abilities of seventh grade students of SMPN 2 Kuripan for the academic year 2020/2021. This type of research was ex-post facto research with a quantitative approach. The population in this study were all seventh grade students of SMPN 2 Kuripan with a total of 126 students. The sampling technique used is a non-probability sampling technique with purposive sampling type. Collecting data used were tests to obtain mathematical communication data and problem solving ability data. Data analysis technique used was Pearson product moment. The results of this study indicated that the level of mathematical communication of class VII C students of SMP Negeri 2 Kuripan in solving math problems on the set material as a whole was in the medium category with an average of 12.3. it was found that 6 students had good communication skills or with a percentage (25%), 8 students had moderate communication skills or with a percentage (33.3) 10 students were less capable or with a percentage (41.7) Problem Solving Communication Level students of class VII C SMP Negeri 2 Kuripan in solving math problems on the set material as a whole was in the medium category with an average of 18.21. it was found that 5 students had good problem-solving abilities or with a percentage (20.8%), 10 students had moderate problem-solving abilities or with a percentage (41.7), 9 students had poor problem-solving abilities or with a percentage (37.5). While the results the hypothesis test was 0.337 indicating that there was no significant relationship between mathematical communication and problem solving abilities of class VII students of SMPN 2 Kuripan for the academic year 2020/2021.